Inhaled or Ingested, Which Is Worse, E-Vaping or High-Fat Diet? - Chen, Hui; Chan, Yik Lung; Thorpe, Andrew E.; Pollock, Carol A.; Saad, Sonia; Oliver, Brian G. (Frontiers in Immunology, 2022)
Long term e-cigarette vaping induces inflammation, which is largely nicotine independent. High-fat diet (HFD) consumption is another cause of systemic low-grade inflammation. The likelihood of using e-cigarettes as a weight control strategy is concomitant with the increase in obesity. In Australia, only nicotine-free e-fluid is legal for sale. Therefore, this study aimed to investigate how nicotine-free e-cigarette vapour exposure affects inflammatory responses in mice with long term HFD consumption. Mice were fed a HFD for 16 weeks, while in the last 6 weeks, half of the chow and HFD groups were exposed to nicotine-free e-vapour, while the other half to ambient air. Serum, lung, liver and epididymal fat were collected to measure inflammatory markers. While both e-vapour exposure and HFD consumption independently increased serum IFN-γ, CX3CL1, IL-10, CCL20, CCL12, and CCL5 levels, the levels of IFN-γ, CX3CL1, and IL-10 were higher in mice exposed to e-vapour than HFD. The mRNA expression pattern in the epididymal fat mirrors that in the serum, suggesting the circulating inflammatory response to e-vapour is from the fat tissue. Of the upregulated cytokines in serum, none were found to change in the lungs. The anti-inflammatory cytokine IL-10 was increased by combining e-vapour and HFD in the liver. We conclude that short-term nicotine-free e-vapour is more potent than long term HFD consumption in causing systemic inflammation. Future studies will be needed to examine the long-term health impact of nicotine-free e-cigarettes.